'Armed Attack' and Article 51 of the UN Charter : Evolutions in Customary Law and Practice - Ruys, Tom (Cambridge : Cambridge University Press, 2010)
This book examines to what extent the right of self-defence, as laid down in Article 51 of the Charter of the United Nations, permits States to launch military operations against other States. In particular, it focuses on the occurrence of an 'armed attack' - the crucial trigger for the activation of this right. In light of the developments since 9/11, the author analyses relevant physical and verbal customary practice, ranging from the 1974 Definition of Aggression to recent incidents such as the 2001 US intervention in Afghanistan and the 2006 Israeli intervention in Lebanon. The notion of 'armed attack' is examined from a threefold perspective. What acts can be regarded as an 'armed attack'? When can an 'armed attack' be considered to take place? And from whom must an 'armed attack' emanate? By way of conclusion, the different findings are brought together in a draft 'Definition of Armed Attack'.
Title from publisher's bibliographic system (viewed on 03 May 2017).
Keywords: Self-defense (International law); Aggression (International law)